Gender Differences in Students’ Spatial Abilities: A Systematic Literature Review Analysis in Educational Contexts - Ningsih, Adi Tia; Handoyo, Budi; Suciptaningsih, Oktaviani Adhi (FKIP Universitas Lampung, 2025)
Abstract: In the midst of increasingly sophisticated technological developments today, spatial ability is one of the important abilities that must be mastered by students. The research is included in the SLR (Systematic Literature Review) research method. Through a literature review of 30 studies, the research sought to identify common patterns, influencing factors, as well as the implications of such gender differences. The analysis showed a tendency for males and females to differ in certain aspects of spatial ability, particularly in tasks involving mental rotation and spatial visualization, with males outperforming females. However, these findings are not always consistent across studies, and various factors such as biological factors such as age, cognitive factors such as learning style, social environmental factors, and individual emotional factors also play an important role that can affect spatial ability. This research also identified a diversity of research methods used in previous studies, ranging from quantitative to qualitative approaches. This demonstrates the complexity of researching this phenomenon. In addition, most of the studies focused on upper secondary students, so further research is needed to understand gender differences in spatial ability at lower levels of education. The findings of this study have significant implications for educational practice. Teachers need to create learning environments that are inclusive and stimulate the development of spatial abilities of all students, regardless of their gender. The use of various learning strategies involving object manipulation, visualization and problem solving can help improve students' spatial abilities. Further research is needed to develop effective interventions to improve spatial ability in all students, study the factors of spatial ability development, conduct cross-cultural studies to study the influence of cultural factors on gender differences in spatial ability. In addition, cross-cultural research is also important to understand how social and cultural factors affect the development of spatial ability. Keywords: spatial ability, spatial ability factors, gender differences.